PERBANDINGAN KAPITALISASI PASAR PORTOFOLIO SAHAM WINNER DAN LOSER SAAT TERJADI ANOMALI WINNER-LOSER - Hadioetomo, Hadioetomo; Sukarno, Agus (Jurnal Keuangan dan Perbankan, 2009)
Capital market anomaly showed that there was an anomaly in efficient capitalmarket hypothesis. One of its types was price reversal phenomenon, which showed that previouswinner portfolio became loser portfolio and vice versa. Price reversal phenomenon was alsoknown as overreaction market hypothesis (OMH). The hypothesis stated that if stock priceswere systematically valued overly as a consequence of investors over pessimism or optimism,price reversal certainly came from previous stock price performance. In this research, theresearcher analyzed price reversal phenomenon on Indonesia Stock Exchange (ISX) by consideringabnormal return. The result of this research indicated that overreaction occur separate in itsmove. Winners and losers were not constant overtime. Analysis independent sample t test didnot show the different average abnormal return significantly so there was anomaly incapitalization market winner and loser.